Preoperative diagnosis of Amyand’s hernia: About 3 cases. - VIGNON, KOSSI CYPRIEN; MUPEPE KUMBA, ALEXIS; NATTA N'TCHA, N'DOME HABIB; ONZO, Roméo; ATTOLOU, SÈTONDJI GILLES ROGER; MEHINTO, KUASSI DELPHIN; DUGUE, LAURENT (My University, 2017)
The Amyand’s hernia, presence of a vermiform appendix in inguinal hernia sac, represents about 0.13% of all acute appendicitis and 1% of all inguinal hernias. Although described more than 250 years ago, his preoperative diagnosis remains exceptional. We report 3 clinical cases of Amyand’s hernia, including a case of right inguinal hernia not strangled and two cases of right inguinal hernia strangled (1 case of recurrent right inguinal hernia strangulated and 1 case of appendicular peritonitis complicating strangulated hernia). An abdominopelvic CT-scan performed in 2 cases/3 allowed the diagnosis to be made. No imaging was performed in the case of recurrent inguinal hernia right strangled; In this case, Amyand’s hernia diagnosis was accidentally made intraoperatively. Laparoscopy localized the vermiform appendix in the hernia sac in the case of appendicular peritonitis complicating strangulated hernia. The 3 patients underwent surgery and the postoperative course was uneventful. Laparoscopy or imaging, especially CT-scanmakes preoperative diagnosis.
Keywords: Amyand’s hernia; C-T scan; Preoperative diagnosis; vermiform appendix